Reconceiving Eliminative Inference. - Forber, Patrick (Philosophy of Science, 2011)
Eliminative reasoning seems to play an important role in the sciences, but should it be part of our best theory of science? Statistical evidence, prevalent across the sciences, causes problems for eliminative inference, supporting the view that probabilistic theories of confirmation provide a better framework for reasoning about evidence. Here I argue that deductive elimination has an important inferential role to play in science, one that is compatible with probabilistic approaches to evidence. Eliminative inferences help frame testing problems, an essential step that determines the context for evaluating statistical evidence. I illustrate this process with examples from molecular evolutionary biology.